2022
DOI: 10.1002/da.23236
|View full text |Cite
|
Sign up to set email alerts
|

The effect of loneliness and social support on the course of major depressive disorder among adults aged 50 years and older: A longitudinal study

Abstract: Background: Previous research indicates that social support, loneliness, and major depressive disorder (MDD) are interrelated. Little is known about the potential pathways among these factors, in particular in the case of adults aged 50 years and older and suffering from MDD. The objective was to investigate whether loneliness mediates the association between low social support and recurrent episodes of MDD. Methods:We used data from a cohort of the Spanish general population interviewed at three time-points o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
1
6
0
1
Order By: Relevance
“…Unsurprisingly, individuals who experienced various dimensions of loneliness, such as feeling left out, feeling isolated, and lacking companionship had approximately 4 to 5 times higher risk of both incident and recurrent depression. This aligns with the substantial body of research that has found loneliness to be a major risk factor for both incident and recurrent depression among older adults [ 15 , 16 , 17 ]. These findings indicate that this pattern has persisted into the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Unsurprisingly, individuals who experienced various dimensions of loneliness, such as feeling left out, feeling isolated, and lacking companionship had approximately 4 to 5 times higher risk of both incident and recurrent depression. This aligns with the substantial body of research that has found loneliness to be a major risk factor for both incident and recurrent depression among older adults [ 15 , 16 , 17 ]. These findings indicate that this pattern has persisted into the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 81%
“…Research conducted early in the pandemic among Canadian adults, 45 to 70 years of age, found that 71.0% of women and 67.4% of men reported feeling lonely in the preceding week [ 14 ]. There is extensive evidence that loneliness in later life is associated with both incident and recurrent depression [ 15 , 16 , 17 ], highlighting concern that the pandemic may contribute to incident depression among those with no history of the disorder, as well as recurrent episodes of depression among those with a lifetime history of depression. Older adults with a history of depression represent a particularly vulnerable subpopulation, as a previous history of depression is a leading risk factor for depression in later life [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence that available social support decreases loneliness among older persons (Chalise et al, 2010; Chen & Feeley, 2014; Chung & Kim, 2022; Gabarrell et al, 2022). In this light, participants completed a 19-Likert-type item measure of social support provided by others incorporating diverse types of such help [tangible help, information-related, emotional support, social integration—see Krause (1990)] ( alpha = .73), modified from Krauss's 27-item version, where eight such items were utilized to assess aspects of loneliness in the present study (see above).…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19] Moreover, lower social support may impede symptom improvement in patients with MDD [20] and predict MDD recurrence. [21] A review in 2020 suggested that a lack of social support is associated with a higher risk of depression after a stroke. [22] These results illustrate the independent correlation between social support and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%